Complementary therapy in palliative care: A synthesis of qualitative and quantitative systematic reviews. (December 2020) - Armstrong, Megan; Kupeli, Nuriye; Flemming, Kate; Stone, Patrick; Wilkinson, Susie; Candy, Bridget
Background: Interventions delivered in palliative care are complex and their evaluation through qualitative and quantitative research can lead to contrasting results. In a systematic review of trials, the effectiveness results of complementary therapies in palliative care were inconclusive; however, our qualitative synthesis showed participants perceived them to be beneficial. Aim: Use a novel methodology to synthesise evidence from qualitative and quantitative systematic reviews on complementary therapy in palliative care to explore the following: (1) If interventions delivered in trials reflect how participants in qualitative studies report they are delivered in real-life settings and (2) whether quality of life measures used in trials capture perceived benefits that are reported in qualitative studies. Methods: Two matrix tables were formulated. In one, key components in delivery of the complementary therapy from the qualitative synthesis which are as follows: (1) relationship with therapist, (2) comfortable environment, (3) choices (e.g. area of massage) and (4) frequent sessions, were plotted against intervention description, to explore matches and mismatches. In the other, items included in quality of life scales were compared with perceived benefits of complementary therapy. Results: None of the trials included all four key delivery components. The five quality of life scales used in the trials failed to capture the range of perceived benefits from the complementary therapies and many included inappropriate or redundant items. Conclusions: By integrating qualitative and quantitative review data, we determined the reasons trials may be inconclusive. This methodological exemplar provides a framework for understanding complexity in outcomes across trials and a direction for future research.